SmO thin films: a flexible route to correlated flat bands with nontrivial topology - Kasinathan, Deepa; Haverkort, Maurits W. (Physical review. B, Condensed matter and materials physics, 2015)
Using density functional theory based calculations, we show that the correlated mixed-valent compound SmO is a three-dimensional strongly topological semimetal as a result of a 4f−5d band inversion at the X point. The [001] surface Bloch spectral density reveals two weakly interacting Dirac cones that are quasidegenerate at the ¯¯¯¯M point and another single Dirac cone at the ¯¯¯Γ point. We also show that the topological nontriviality in SmO is very robust and prevails for a wide range of lattice parameters, making it an ideal candidate to investigate topological nontrivial correlated flat bands in thin-film form. Moreover, the electron filling is tunable by strain. In addition, we find conditions for which the inversion is of the 4f−6s type, making SmO to be a rather unique system. The similarities of the crystal symmetry and the lattice constant of SmO to the well studied ferromagnetic semiconductor EuO, makes SmO/EuO thin film interfaces an excellent contender towards realizing the quantum anomalous Hall effect in a strongly correlated electron system.
Gesehen am 20.09.2017